The Influence of Wordwall Learning Media on Student Learning Results in Class III Islamic Religious Education Subjects at SDN Telaga Murni 02 - Anjar Dwi Ariani; Iwan Hermawan; Nur Aini farida (al-Afkar, Journal For Islamic Studies, 2025)
This study is outlined behind by the existence of a problem in the SDN telaga Murni 02 which is a problem with learning results. The objectives of this research are: 1) to determine the effectiveness of using Wordwall learning media on the learning outcomes of students in Islamic Education subjects at SDN Telaga Murni 02, 2) to identify the learning outcomes of students at SDN Telaga Murni 02, 3) to determine whether there is an effect of using Wordwall learning media on the learning outcomes of students in Islamic Education subjects at SDN Telaga Murni 02. This research uses a quantitative approach with an experimental method, employing a quasi-experimental design with a non-equivalent control group. The population in this study comprises all third-grade students at SDN Telaga Murni 02. The sample in this research includes two classes, designated as the control class and the experimental class. Data collection techniques used in this research are tests and documentation. The test instruments used are pre-tests and post-tests. Based on the results of the independent sample t-test in the experimental and control classes, the significance value is 0.038, which means it is < 0.05, thus H0 is rejected and Ha is accepted. It can be concluded that there is a difference in the average learning outcomes of students using Wordwall learning media compared to conventional learning without using Wordwall learning media in Islamic Education subjects.